BIBLIOMETRIC STUDY ON THE IMPORTANCE OF ENDPOINT SECURITY IN COMPANIES - Gonçalves, João (2023)
This bibliometric study addresses the importance of endpoint security in companies, considering the growing use of information technologies, both in business and personal use. It highlights the need to protect endpoints such as computers, mobile devices, servers, and IoT devices. Endpoint security encompasses measures such as monitoring the files and binaries on and running on the machine using antivirus, data encryption, and threat detection solutions. The literature review highlights the importance of terminology and best practices, highlighting the application of graph-based approaches to strengthen security in medical information networks. Tools such as EDR are cited as essential, especially for small and medium-sized companies. The study emphasizes the importance of business continuity in the face of cyber threats, highlighting the role of artificial intelligence, machine learning, and frameworks. It takes a bibliometric approach, using a specific database to collect bibliometric data on scientific publications published between 2017 and 2023. As a basis for the study, the words “cybersecurity”, “endpoint security”, “business continuity”, and “business” were used. Various analyses of bibliometric results are also presented, including the number of publications by type of document, the scientific journals with the highest number of publications, the countries with the highest number of publications, the number of publications per author, the most cited articles, and the occurrence of identified keywords.